2002
DOI: 10.1093/jhered/93.1.52
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Qualitative Traits in Domesticated Chia (Salvia hispanica L.)

Abstract: In Salvia hispanica L., several changes in qualitative characters, including seed coat color, stem pigmentation, and shattering, have evolved with cultivation and domestication. Three F(2) segregating generations from crosses between wild and domesticated parents were scored for three qualitative traits. A single recessive gene, designated scc, was found to govern the white seed characteristic. A single dominant gene, designated SSP, was found to control striated stem pigmentation. A complete dominance of open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 8 publications
0
26
0
Order By: Relevance
“…Both genotypes have been classified previously as domesticated, based on the presence of human-selected traits: higher seed mass, closed calyces that prevent seed shattering and dispersal, and determinacy of flowering and seed set described by Cahill and Provance and HernandezGomez et al [6,8,9].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both genotypes have been classified previously as domesticated, based on the presence of human-selected traits: higher seed mass, closed calyces that prevent seed shattering and dispersal, and determinacy of flowering and seed set described by Cahill and Provance and HernandezGomez et al [6,8,9].…”
Section: Methodsmentioning
confidence: 99%
“…However, chia commercialized today is mainly black-spotted, followed by a low but increasing percentage of white seeds [1]. As was demonstrated by Cahill and Provance [6], single genes govern seed coat color and stem pigmentation; a single recessive gene, designated scc, was found to govern the white seed characteristic.…”
Section: Introductionmentioning
confidence: 99%
“…1). A single dominant gene, known as SSP, is responsible for controlling the striated stem pigmentation (Cahill & Provance, 2002).…”
Section: Chia Seed Description and Compositionmentioning
confidence: 99%
“…Cahill also found that seed size was larger in cultivated chia than in wild germplasm and was a part of a gigantism syndrome in advanced domesticated chia lines, as well as allelopathy. In a study of inheritance of three qualitative traits in chia, Cahill and Provance (2002) found that genes for open calyces, charcoal seed color, and pigmented stems are dominant over genes for closed calyces, white seed color, and nonpigmented stems.…”
Section: Genetic Diversity and Breedingmentioning
confidence: 99%
“…Making chia crosses is considerably easier when dominant phenotypic markers are available. Cahill and Provance (2002) used stem striation/pigmentation as a dominant marker. Breeding efforts at the University of Kentucky have used flower color as a dominant marker.…”
Section: Genetic Diversity and Breedingmentioning
confidence: 99%